Teknik Perbaikan Terus-Menerus (Continuous Improvement Techniques), Pentingnya Partnership dan Pengaruhnya terhadap Kinerja Operasional Perusahaan - Ellitan, Lena (Jurnal Widya Manajemen & Akuntansi, 2005)
Manufacturing excellence often results from the combined successive incremental improvement techniques and capital investment in technology. This research focuses successive incremental improvement techniques that considered as success factor of firms' competitive advantage.